PERAN SERIKAT PEKERJA DALAM MENINGKATKAN KUALITAS DAN PENGEMBANGAN SUMBER DAYA MANUSIA ANGGOTA SERIKAT SAAT MENGHADAPI TANTANGAN DI ERA GLOBALISASI: Studi Kasus Serikat Pekerja Nasioal Kabupaten Serang - Saepulloh, Asep; Diantoro, Eman; Laksana, April (Gapenas Publisher, 2024)
This research explores the role of trade unions in enhancing the quality and development of human resources (HR) in the context of globalization and digitalization challenges. Facing the dynamics of labor market changes and rapid technological advancements, the role of trade unions becomes increasingly important in maintaining employee welfare and competitiveness. Using a qualitative approach, this study analyzes how trade unions can influence company policies related to training and skill development, wage negotiations, and the creation of a harmonious work environment. The findings of the study indicate that trade unions serve as the primary advocates for employee rights, ensuring that employees have fair access to skill development programs and training relevant to current market needs. Moreover, trade unions play a crucial role in facilitating dialogue between management and employees, contributing to the creation of more inclusive and responsive work policies in the face of global challenges. Trade unions also face challenges in adjusting their strategies to the trends of digitalization, which require the enhancement of digital skills and adaptation to technological changes